Immune Function (serum IL-4 and IL-5), Nutritional Status, and Clinical Outcomes in Children with Bronchial Asthma after vitamin D supplementation: serum IL-4 and IL-5 in Children with Bronchial Asthma - Xiao, Xiangli; Wang, Ranran; Qin, Li (Journal of Medical Biochemistry, 2025)
Background: Bronchial asthma (BA) is a common chronic respiratory condition in children, characterized by recurring episodes of airway inflammation, wheezing, and breathing difficulties. Immune dysfunction and malnutrition often complicate the disease, worsening its severity and increasing the risk of recurrence. Despite ongoing treatment advancements, there is no definitive cure for BA, and management primarily revolves around symptom control and improving overall health. This study explores the combined therapeutic effects of pediatric massage and vitamin D supplementation on the nutritional status, immune function (serum IL-4 and IL-5 ) , and clinical outcomes in children with BA. Methods: A total of 60 children diagnosed with BA were randomly assigned to one of two groups: a control group receiving conventional treatment alone, and an experimental group receiving conventional treatment alongside pediatric massage and daily vitamin D supplementation. Both groups were monitored over a two-month period for changes in clinical symptoms, immune markers (CD3+, CD4+, CD4+/CD8+ ratio), nutritional protein levels (albumin, transferrin, prealbumin, and total protein), and recurrence rates. Results: The experimental group showed significantly faster symptom relief and improved immune function compared to the control group. This included enhanced immune markers, such as increased CD3+ and CD4+ counts and an improved CD4+/CD8+ ratio. Nutritional status also improved, as evidenced by higher levels of albumin, transferrin, prealbumin, and total protein. Additionally, the recurrence rate in the experimental group was notably lower (10%) compared to the control group. The experimental group also exhibited reduced levels of inflammatory cytokines, including IL-4 and IL-5, suggesting a beneficial effect on immune modulation. Conclusion: The combination of pediatric massage and vitamin D supplementation significantly improves clinical outcomes in children with BA, enhancing immune function, nutritional status, and reducing the recurrence rate. This adjunctive therapy shows promise in managing BA in pediatric patients and warrants further investigation for its long-term effectiveness.